Relationship between the fundamental frequency and mean air flow rate - Asha G.G (Journal of All India Institute of Speech and Hearing, 1970)
The air flow and vocal cord vibration plays an important role in determining the pitch and intensity. A single aspect of voice production such as pitch should notbe evaluated in isolation but as part of the voice production system and the relation" ship between flow rate and pitch must be given due significance.